2011
DOI: 10.1111/j.1872-034x.2011.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of hepatic intercellular adhesion molecule‐1 expression in Egyptian infants with biliary atresia and other forms of neonatal cholestasis

Abstract: These results suggest that ICAM-1 has a diagnostic value in patients with BA and would be a promising helpful tool when investigating patients with NC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
11
2
Order By: Relevance
“…Importantly, the staining pattern of YAP is both strong and diffuse. YAP staining also appears to be the most sensitive and specific IHC markers tested as ancillary tools in the differential diagnosis of BA versus non-BA neonatal cholestasis 9,11,12 . The extent and intensity of YAP expression appears to be highly dependent on the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the staining pattern of YAP is both strong and diffuse. YAP staining also appears to be the most sensitive and specific IHC markers tested as ancillary tools in the differential diagnosis of BA versus non-BA neonatal cholestasis 9,11,12 . The extent and intensity of YAP expression appears to be highly dependent on the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…General epithelial markers such as CK7 and CK19 stain biliary epithelium but not the newly emergent, proliferating bile ductules 10 . Alternatively, neural cell adhesion molecule (NCAM/CD56) 9 and intercellular adhesion molecule 1 (ICAM-1) 12 can stain both the existing bile ducts and the newly-formed bile ductules, but mark these bile ductules in a somewhat weak and non-specific fashion. The cytoplasmic/membranous staining pattern of both markers can be difficult to optimize and interpret.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, ICAM-1 expression has previously been shown to be upregulated within BA liver tissue[51] and a recent study from Egypt identified elevated sICAM-1 levels in BA patients compared to controls. [52] In addition, analysis of polymorphisms of the ICAM-1 gene in BA discovered that the ICAM G241R polymorphism was significantly associated with BA, suggesting that this polymorphism plays a role in disease pathogenesis. [53] ICAM-1 is an adhesion molecule that is expressed on cells of multiple lineages at sites of inflammation and mediates leukocyte and granulocyte migration through endothelial cells as well as promotes antigen-specific T cell proliferation.…”
Section: Evidence For Dysregulation Of Adaptive Immunity In Biliary Amentioning
confidence: 99%
“…We have previously studied different proinflammatory molecules such as intercellular adhesion molecule-1 [6], CD56 [7], and P-selectin [8] and different proinflammatory cytokines such as IL-2 and IL-8 [9] in BA and described their relation to the disease process.…”
Section: Introductionmentioning
confidence: 99%